Semialgebraic groups over real closed fields (2017)
This thesis investigates semialgebraically connected semialgebraic groups over a sufficiently saturated real closed field R = R = (R, <, +, 0, ., 1) and is therefore contribution to the study of definable groups o o-minimal structures.